Impact of using the International Risk Scoring Tool on the cost-utility of palivizumab for preventing severe respiratory syncytial virus infection in Canadian moderate-to-late preterm infants. (31st December 2023) - Rodgers-Gray, Barry S.; Fullarton, John R.; Carbonell-Estrany, Xavier; Keary, Ian P.; Tarride, Jean-Éric; Paes, Bosco A.
Abstract: Background and objective: To assess the cost-utility of palivizumab versus no prophylaxis in preventing severe respiratory syncytial virus (RSV) infection in Canadian moderate-to-late preterm (32–35 weeks' gestational age) infants using an (i) International Risk Scoring Tool (IRST) and (ii) Canadian RST (CRST). Methods: A decision tree was developed to assess cost-utility. Infants assessed at moderate- and high-risk of RSV-related hospitalization (RSVH) by the IRST or CRST received palivizumab or no prophylaxis and then progressed to either (i) RSVH; (ii) emergency room/outpatient medically attended RSV-infection (MARI) or (iii) were uninfected/non-medically attended. Infants admitted to intensive care could incur mortality (0.43%). Respiratory morbidity was accounted in all uninfected surviving infants for 6 years or 18 years (RSVH/MARI). Palivizumab efficacy (72.2% RSVH reduction) and hospital outcomes were from the Canadian CARESS, PICNIC and RSV-Quebec studies. Palivizumab costs (50 mg: CAN752; 100 mg: 1, 505) were calculated from Canadian birth statistics combined with a growth algorithm. Healthcare/payer and societal costs (May 2022; 1.5% discounting) were included. Results: Cost per quality-adjusted life year (QALY) was 29, 789 with the IRST (0.79 probability of being <50, 000) and 15, 833 with the CRST (0.96 probability). The model was most sensitive to utility scores, long-term sequelae and palivizumab cost. Vial sharing improved the incremental cost-utility ratio (IRST: 22, 319; CRST: 9, 231). Conclusions: Palivizumab was highly cost-effective ( vs no prophylaxis) in Canadian moderate-to-late preterm infants using either the IRST or CRST. The IRST has fewer risk factors than the CRST (3 vs 7, respectively), captures more potential RSVHs (85% vs 54%) and provides another option to guide cost-effective RSV prophylaxis in Canada. Graphical Abstract: UF0001